Excipients of inhaled medications with potential to cause adverse reactions - Kusonić Dejan Ž.; Petronijević Katarina Z.; Čanji-Panić Jelena M.; Pavlović Nebojša M.; Todorović Nemanja B.; Srđenović-Čonić Branislava U.; Šušnjević Sonja Lj; Lalić-Popović Mladena N. (Srpsko lekarsko drustvo, 2021)
Introduction: In addition to the active pharmaceutical ingredient (API), the composition of the medicines also includes excipients which are only ideally completely pharmacologically inactive. It has been shown that excipients in inhaled preparations can cause effects opposite to the pharmacological effect of the medicine. Aim: The Aim of the study was to identify potentially harmful excipients in inhaled medicines approved in the Republic of Serbia. Material and Methods: The academic study was conducted during April 2021 and included the analysis of medicines that received a marketing authorization from the Medicines and Medical Devices Agency of Serbia (ALIMS). Qualitative compositions of inhaled medicines available in Summaries of product characteristics (SmPC) on the ALIMS's official website were observed. Excipients considered potentially harmful if they are recognised as excipients with known effect (EKE) in Serbian and European regulations. Results: Total of 46 inhalation preparations that are approved in Serbia were analyzed. In their composition were found 17 different excipients. By comparing appropriate domestic and European regulations three excipients from examined preparations that represent potential causative agents of adverse drug reactions (ADRs) were identified: lactose-monohydrate, ethanol and benzalkonium chloride. It has been shown that disodium EDTA is also a potential causative agent of ADRs, but it is not classified as EKE. Conclusion: Neither domestic nor international regulations have classified EDTA and its salts as EKE and they should be given special attention in the future as potential causative agents of ADRs. It has been shown that benzalkonium chloride is the only excipient that can lead to bronchospasm and it was found in two inhaled medicines.